2020
DOI: 10.1002/adfm.202003851
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Solidification Induced by Active Janus Particles

Abstract: Crystals melt when thermal excitations or the concentration of defects in the lattice is sufficiently high. Upon melting, the crystalline long-range order vanishes, turning the solid to a fluid. In contrast to this classical scenario of solid melting, here a counter-intuitive behavior of the occurrence of crystalline long-range order in an initially disordered matrix is demonstrated. This unusual solidification is demonstrated in a system of passive colloidal particles accommodating chemically active defects-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
(72 reference statements)
1
27
0
Order By: Relevance
“…The mechanism of motion for Ag/AgCl/PS micromotors was previously discussed in the literature [ 33 , 34 , 38 ], wherein it was shown that the Janus particles are driven by the decomposition of AgCl, which is supported by plasmonic excitations in Ag clusters. The reaction triggers the simultaneous release of protons and Cl ions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of motion for Ag/AgCl/PS micromotors was previously discussed in the literature [ 33 , 34 , 38 ], wherein it was shown that the Janus particles are driven by the decomposition of AgCl, which is supported by plasmonic excitations in Ag clusters. The reaction triggers the simultaneous release of protons and Cl ions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, additional examination of active phase behavior in 3D may prove insightful for further understanding the role of dimensionality in the rich phase behavior (such as "bubbly liquids" [31,88,89]) reported in 2D. Finally, while active freezing has primarily been experimentally interrogated in 2D [90][91][92], we hope that our study will aid in guiding ongoing efforts [93] to realize 3D active crystals.…”
mentioning
confidence: 88%
“…More recently, in ref. [138] visible-light-driven Ag/AgCl− based Janus particles have been fixed to a glass substrate such that they do not move but create a phoretic field which acts on the particles in their vicinity. When embedding the Janus particles, here called "active defects", in a "matrix" of passive colloids at moderate density (where they form an amorphous state with a liquid-like structure), they repel the SiO 2 colloids and push them together which leads to crystallization.…”
Section: Cross-interactionsmentioning
confidence: 99%